Disseminated Sporotrichosis with Cutaneous and Osteoarticular Involvement in an Immunosuppressed Patient: A Case Report - Teodoro, Victória Cassioti; Duran, Yasmin; Kajita, Mariana Soares; Sarmento, Arthur Moura; Fujiki, Renato Toshio Murashita; Lindoso, José Angelo Lauletta (Brazilian Journal of Case Reports, 2026)
Sporotrichosis is a fungal infection caused by species of the Sporothrix genus, primarily Sporothrix schenckii and Sporothrix brasiliensis, the latter being more virulent and associated with higher transmission rates in Brazil. Infection generally occurs through traumatic inoculation of contaminated soil, plants, or organic matter and may also be transmitted by cats, particularly in cases involving S. brasiliensis. The disease predominantly affects the skin and subcutaneous tissue. We report the case of a young man living with HIV/AIDS who presented with cutaneous lesions and osteoarticular involvement caused by Sporothrix spp., consistent with disseminated sporotrichosis. The patient had a history of contact with cats. The diagnosis was confirmed by skin and bone biopsies, with polymerase chain reaction (PCR) positive for Sporothrix. During treatment, which included antiretroviral therapy, the patient developed immune reconstitution inflammatory syndrome (IRIS) and worsening renal function associated with the use of amphotericin B deoxycholate. Treatment was prolonged, with outpatient follow-up and subsequent therapy with itraconazole. Sporotrichosis is an emerging disease in Brazil, and its variable clinical presentation may delay diagnosis. It should be considered in the differential diagnosis of chronic cutaneous lesions, particularly in immunosuppressed individuals, because of the risk of disseminated disease and osteomyelitis.